(untitled) (Indian Journal of Animal Production and Management, 2013)
A field survey was conducted to know the existing feeding and housing management practices by buffalo farmers in rural, semi-urban and urban areas of Krishna district. It was found that only 1.6 % farmers practiced chaffing of fodder. Paddy straw was sole roughage to buffaloes. No farmer practiced silage making and urea treatment of paddy straw. 26, 42 and 68% farmers offered purchased concentrate feed, 80, 94 and 88 % offered concentrate in soaked form in rural, semi-urban and urban areas, respectively. Regarding housing practices 83, 67 and 56% farmers’ maintained buffaloes in loose house: 38, 51 and 68% had pucca floor: 23, 36 and 60% had pucca drainage facilities in rural, semi-urban and urban areas. 20% farmers provided cooling devices like fan in urban areas of the district. High cost of pure bred buffaloes, hired labour, feed ingredients, lack of financial assistance for purchase of high milk producing buffaloes and equipment like chaffer cutter and lack of extension activities was the major problems.